The adventures of Tintin : Land of black gold Volume 5 - Hergé (New York Little, Brown, 2008)
In volume 5, readers will witness Tintin and his team discovering new and interesting things around the world. From exploring exotic lands to solving thrilling mysteries, Tintin faces constant challenges and dangers. This book promises to bring readers a dramatic and exciting experience, with the perfect combination of action, humor and intelligence in solving problems.
Keywords: Tham khảo